Quality Value based Routing protocol for Energy Optimization in Wireless Sensor Networks - et al., Dasari Naga Raju (International Journal of Advanced Science and Technology, 2019)
From the past decade, wireless sensor networks (WSNs) raised their importance in the communication networks. Though WSNs are having the many advantages, they are lacking in efficient routing protocols. This paper considers the objective of optimizing the energy of WSNs. The proposed method considers the quality value of each node to forward the packers. The quality value is depends on the residual energy and cost. The cluster head selection is also done by the quality value of the node. The simulation analysis is performed with different parameters. The results proved the efficiency of the proposed protocol.